Hipótesis, citas, resultados: reflexiones sobre la comunicación científica en didáctica de ciencias - Jiménez Aleixandre, María Pilar; García-Rodeja, I. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1997)
This paper raises a reflection on the role of scholarly papers in the dissemination of research in Science Education, and in the discussion about educational theories. The convenience of a rigorous distinction in each paper between what are hypotheses or opinions, what are evidences, experimentally tested, and what constitutes a metanalysis from literature review, is suggested. These suggestions attempt to improve the quality of scientific communication in the community doing research in Science Education.